PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI ENERGY EDUCATION BERBASIS SMART APPS CREATOR PADA MATERI SUMBER ENERGI DI SEKOLAH DASAR - Moch Zaidan Akmal M; Irvan Permana; Dita Destiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to develop products and determine the feasibility of learning media for energy education applications based on smarts app creator on energy source material. The method used in this research is a research and development method known as Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research begins with analyzing the needs of students, then making a learning media design for the smarts app creator-based energy education application, then conducting expert validation and product revision. Research results from the validation of 88% media experts, 100% language experts and 96% material experts, show that the learning media for smarts app creator-based energy education applications are very feasible to use with an average percentage of 94%. At the implementation stage, 35 students gave a very good response to the smarts app creator-based energy education application used by obtaining an average percentage of 89% which means it is very feasible to use. Therefore, it can be concluded that the development of learning media for energy education applications based on smarts app creator on the material of energy sources in daily life at Dayeuhluhur CBM Elementary School, Sukabumi City in class lV A at the end of the even semester of 2023/2024 is very feasible to use during the learning process.